2020
DOI: 10.3389/fimmu.2020.00211
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome—A Key Player in Antiviral Responses

Abstract: The NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome is an oligomeric complex comprised of the NOD-like receptor NLRP3, the adaptor ASC, and caspase-1. This complex is crucial to the host's defense against microbes as it promotes IL-1β and IL-18 secretion and induces pyroptosis. NLRP3 recognizes variety of pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs) generated during viral replication that triggers the NLRP3 inflammasome-dependent antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
324
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(327 citation statements)
references
References 77 publications
1
324
0
2
Order By: Relevance
“…31 Most viruses increase their proliferation and survival via an increase in the NLRP3 inflammasome, 32 with the regulation of the NLRP3 inflammasome being taken over by viruses. 33 As melatonin is a significant inhibitor of the NLRP3 inflammasome, 34 the suppression of melatonin production, both pineal and mitochondrial, by viruses is likely to be an important aspect of how viruses disengage the NLRP3 inflammasome from physiological processes. It should also be noted that IL-18 is induced along with IL-1β from NLRP3 inflammasome activation, with IL-18…”
Section: Circadian Rhythm and Mitochondrial Metabolismmentioning
confidence: 99%
“…31 Most viruses increase their proliferation and survival via an increase in the NLRP3 inflammasome, 32 with the regulation of the NLRP3 inflammasome being taken over by viruses. 33 As melatonin is a significant inhibitor of the NLRP3 inflammasome, 34 the suppression of melatonin production, both pineal and mitochondrial, by viruses is likely to be an important aspect of how viruses disengage the NLRP3 inflammasome from physiological processes. It should also be noted that IL-18 is induced along with IL-1β from NLRP3 inflammasome activation, with IL-18…”
Section: Circadian Rhythm and Mitochondrial Metabolismmentioning
confidence: 99%
“…Hence, treatments targeting in ammasome (colchicine), COX-2 (aspirin, ibuprofen, indomethacin) and IL-1 (anakinra) constitute the treatments options for idiopathic pericarditis [6]. Viral components and cytosolic danger signals, such as mitochondrial injury, protein aggregates, and aberrant ion concentrations can activate NLR Family Pyrin Domain Containing 3 in ammasome which in turn releases IL-1β, IL-18 and the propyroptotic factor gasdermin D [7]. In a previous study, SARS-CoV-2 has been shown to activate the NLRP3 in ammasome and induce the production of IL-18 by human macrophages by its ion channel-forming E protein and ORF8b, which are also the structural components of SARS-CoV-2 [1].…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells can rapidly sense a viral infection via a group of proteins that upon sensing viral associated molecular patterns (PAMPs) are able to form a cytosolic multiprotein inflammasome complex. These complexes in turn promote a proteolytic cleavage and secretion of pro-inflammatory cytokines like interleukin 1β (IL-1β) and interleukin 18 (IL-18) [ 75 ]. In addition to these cytokines, the activated inflammasome also causes extracellular release of the HMGB1 protein, which amplifies the inflammatory process [ 76 ].…”
Section: Va Rnamentioning
confidence: 99%